Community: ecological and ecumenical - Rolston, Holmes, 1932-2025, author; Iliff Theological Seminary (Denver), publisher (Colorado State University. Libraries, 1973)
The era of ecology brings a vision of one world environmentally. The ecumenical movement hopes for a community and dialogue of faiths. Both have a common etymological root in the Greek word "oikos," household. These two contemporary concerns, one in science, one in religion, offer the possibility of a more comprehensive sense of community. In the Bible, the earliest sin is ecological, humans despise their garden earth, and the sin of brother against brother follows. Our charge is to live on earth and keep it. Keeping Eden requires that we be our brothers's keeper.
Keywords: Eden earth; ecumenics; ecumenical movement; ecology; ecological crisis; reconciliation